The mental health impact of AIDS-related mortality in South Africa: a national study. Issue 4 (15th December 2008) - Myer, L; Seedat, S; Stein, D J; Moomal, H; Williams, D R
Abstract : Background: Few data exist on how the HIV/AIDS epidemic may influence population mental health. The associations were examined between knowing someone who died of HIV/AIDS and common mental disorders among South African adults. Methods: Between 2002 and 2004, a nationally representative sample of 4351 adults were interviewed about personally knowing someone who died of HIV/AIDS, and the World Health Organization Composite International Diagnostic Interview was used to generate psychiatric diagnoses for depression, anxiety and substance abuse disorders during the preceding 12 months based on the Diagnostic and Statistical Manual, 4th edition (DSM-IV). Results: Overall, 42.2% of the sample knew someone who died of HIV/AIDS, and 16.5% met the criteria for at least one DSM-IV diagnosis. Individuals who knew someone who died of HIV/AIDS were significantly more likely to have any DSM-IV defined disorder, including any depressive, anxiety or substance-related disorder (p<0.001 for all associations). In multivariate models adjusted for participant demographic characteristics, life events and socioeconomic status, individual disorders significantly associated with knowing someone who died of HIV/AIDS included generalised anxiety disorder, social phobia and alcohol/drug dependence or abuse. Based on these results, it is estimated that up to 15% of 12-month DSM-IV disorders in the South African adult population may be related to knowing someone who died of HIV/AIDS. Conclusion: These novel data suggest that AIDS-related mortality may contribute substantially to the burden of mental disorders in settings of high HIV prevalence. While this finding requires further investigation, these data suggest the need to strengthen mental health services in communities where HIV/AIDS is prevalent.